Implementasi Metode Praktikum terhadap Keterampilan Proses Sains Siswa Kelas IV pada Pembelajaran IPA Sekolah Dasar - Salam Salam (Journal on Education, 2024)
The skills required to engage in scientific processes include cognitive, manual, and social skills. Laboratory practice is an effective way to develop generic skills in planning, execution, and reporting. This study aims to identify students' science process skills during laboratory practice by involving 20 students. This research uses mixed methods, combining qualitative and quantitative approaches, with observation sheets and Student Worksheets (LKPD) as instruments. The observed aspects cover six skills: observing, classifying, predicting, communicating, measuring, and concluding. The research results indicate: 1) Observing; students use their senses very well (88.685%). 2) Classifying; students gather facts well (87.5%). 3) Predicting; students predict events well (83.75%). 4) Communicating; students organize data and report clearly (83.81%). 5) Concluding; students conclude phenomena well (82.375%). 6) Measuring; students use tools very well (90 Overall, the fourth-grade students at SD Negeri 1 Lawela achieved KPS scores in the "very good" category, with a percentage of 85.81%.